Efeitos de um programa de fortalecimento muscular do tornozelo e estímulos sensoriais cutâneos plantares em idosos com Diabetes Mellitus tipo 2 : ensaio clínico aleatório - Peternella, Fabiana Magalhães Navarro (2016)
Diabetes Mellitus (DM) can trigger sensory motor complications in the feet, damaging the plantar sensitivity, balance and gait of the elderly. Analyze the effect of a muscular ankle strengthening intervention and feet sensory stimuli for gait speed and posture balance in elders with Diabetes Mellitus type 2. Cross - sectional study with 187 elderly patients (60 years old or older) with DM2 enrolled in a Basic Health Unit of Maringá - Paraná State. The clinical condition of the feet, physical activity level, plantar cutaneous sensitivity and Diabetic Foot Risk Rating were evaluated. A randomized clinical trial was conducted with 37 of the 66 elderly, with 17 elderly randomly selected for the intervention group (G1) and 20 elderly for the control group (G2). The intervention lasted for 12 weeks, with a frequency of 2X / week and consisted of guidance on foot care and exercises to strengthen the plantiflexor and dorsiflexor muscles with theraband, proprioceptive exercises on the rocker and proprioceptive buoy, and sensorial stimuli in the plantar region with bristle brush and fabric. The G2 received only foot care guidance. The variables analyzed were cutaneous plantar sensitivity, peak torque, postural balance and walking speed. T-test was applied for intra-group difference (mean difference and standard deviation) and difference between groups (difference of means and 95% CI), considering significance for p <0.05. In relation to factors associated with loss of skin-plantar sensitivity in elderly patients with peripheral neuropathy, the low income (p <0.001) and the absence of family background of DM (p <0.004) was associated with the loss of skin-plantar sensitivity and low-income with the risk of diabetic foot (p <0.018). Regarding the overall health of the feet, the presence of calluses is associated with loss of skin-plantar sensitivity (p <0.002) and the risk of diabetic foot (p <0.006). For to differences between genders in relation to factors associated with the risk of diabetic foot in elderly persons, most (58.6%) were female and among them the risk factors for diabetic foot were older age (p<0.021; OR 6.0), presence of calluses (p<0.046; OR 2.83) and claw toes (p<0.041; OR 3.18). And among men, insulin use (p<0.008; OR 5.22), presence of sensory comorbidities (p<0.007; OR 5.0), ulcers (p<0.001), numbness (p<0.002; OR 6.6) and stiffness in the feet (p<0.009; OR 5.44). It was observed that the first group showed improvement of the cutaneous plantar sensitivity of the right foot (DM: 5.87 points, 95% CI 2.38 to 9.36) and left foot (DM: 6,10, 95% CI 1,91 to 10,29), increased gait speed (DM: 0,18; 95% CI 0,34 to 0,03) and increased plantar flexion torque of the left foot (DM: 19,43; 95% CI 1,22 to 37,65). No significant differences were found for the torque of dorsiflexion and right foot plantiflexion, and in the static balance. The kinesiotherapy and sensory stimuli program was effective in improving plantar skin sensitivities of both feet, in gait velocity and in the left foot plantiflexion torque of elderly patients with DM2. Elderly people with diabetic neuropathy, especially those with low income, need more attention from health professionals, with emphasis on the orientation and supervision of foot care. The factors associated with the development of diabetic foot presented differently between women and men, requiring a targeted and more specific preventive approach.